Case report: A case of Rabson–Mendenhall syndrome: long-term follow-up and therapeutic management with empagliflozin - Foglino, R.; Barbetti, F.; Morotti, E.; Castorani, V.; Rigamonti, A.; Frontino, G.; Barera, G.; Bonfanti, R. (Frontiers in Genetics, 2024)
Background: Rabson Mendenhall Syndrome (RMS), a rare disorder characterized by severe insulin resistance due to biallelic loss-of-function variants of the insulin receptor gene (INSR), presents therapeutic challenges (OMIM: 262190). This case study explores the efficacy of adjunctive therapy with sodium-glucose co-transporter 2 inhibitors (SGLT2i) in the management of RMS in an 11-yearold male patient with compound heterozygous pathogenic variants of INSR.Methods: Despite initial efforts to regulate glycemia with insulin therapy followed by metformin treatment, achieving stable glycemic control presented a critical challenge, characterized by persistent hyperinsulinism and variable fluctuations in glucose levels. Upon the addition of empagliflozin to metformin, notable improvements in glycated hemoglobin (HbA1c) and Time in Range (TIR) were observed over a ten-month period.Results: After 10 months of treatment, Empagliflozin therapy led to a clinically meaningful reduction in HbA1c levels, decreasing from 8.5% to 7.1%, along with an improvement in Time in Range (TIR) from 47% to 74%. Furthermore, regular monitoring effectively averted normoglycemic ketoacidosis, a rare complication associated with SGLT2 inhibitor therapy.Conclusion: This case highlights the potential of SGLT2i as adjunctive therapy in RMS management, particularly in stabilizing glycemic variability. However, further research is warranted to elucidate the long-term efficacy and safety of this therapeutic approach in RMS and similar insulin resistance syndromes.